Detecção de inibidores de proteinases cisteínicas em raízes de feijão-de-corda [Vigna unguiculata (L.) Walp.] e avaliação de sua atividade sobre o nematóide das galhas Meloidogyne javanica. - Monteiro Júnior, José Edvar (2007)
Detection of cysteine proteinase inhibitors in cowpea[Vigna unguiculata(L.) Walpers] roots as well as the accumulation of inhibitors enriched fractions throughammonium sulfate precipitation followed by reversed-phase liquid chromatography were in this present work accomplished. Fractions containing higher levels of cysteine proteinase inhibitor activity were selected and subjected to evaluation of its ability of to suppress the mobility of second stage juveniles (J2) of the root-knot nematode Meloidogyne javanica, race 1. In addition, the nematicidal effect of these fractions was also tested. When the mobility parameter was analyzed the ammonium sulfate precipitated F 30/60 fraction, at a dose of 40 μg of proteins, it shown to be the most potent of all tested samples at 24 h after incubation. However, regarding to mortality the both picks, PIHPLC and PIIHPLC, obtained from the HPLC step were the more actives causing a percentage of killing nematodes of 95.0 % and 94.2 %, respectively when the most potent doses of these picks were compared. Moreover, FITC-coupled F 30/60 fraction was used in light-flu orescence microscopy experiments in order to answer the following basic questions: 1) the observed effects on mobility and mortality will be related to the binding of the proteins in the nematode? And 2) If yes, this interaction is performed with the gut or surface nematode, or yet in the both structures? F 30/60 fraction appears to be incorporated by juveniles and specifically bind to the region corresponding to the gut of nematodes at 6 h after incubation, while at 24 h after incubation the fluorescent complex appears to be widespread along the whole body of the nematode, as observed by light-fluorescence microscopy. These results, all together, suggest the possible use of the inhibitors present in cowpea roots as a potential biological tool in the control of the root-knot nematode, M. javanica.